“De tecelã de fato à ‘Hora do Pato’, eu fiquei seu fã” : a trajetória de Ângela Maria, de crooner a cantora consagrada através da Revista do Rádio - Vaz Neto, Raimundo Cézar (2023)
This research aims to problematize the professional trajectory of the popular singer of radio and Brazilian Ângela Maria (1929-2018), having as its source the extinct Revista do Rádio do Rio de Janeiro, between the years 1951 to 1970, consulting the collection in the Digital Library Of the National Library. Our methodology is based on the theorists of the New Cultural History, through bibliographic research, situating the press illustrated in Brazil, to get to Revista do Rádio and how it fueled the curiosity of the singer's fans, in addition to shows, trips, radio programs and television, insinuating, informing and provoking the expanded trajectory of the artist in its various phases. About the repertoire, composers/composers, radio and TV programming, we dialogue with historians Alcir Lenharo (1995), Lia Calabre (1996; 2002; 2004), Adalberto Paranhos (2005) and Maria Izilda Santos de Matos (1996). About the Brazilian press, its evolutions, heritages, contours, changes and failures, we built parallels with the studies of Pâmela Keiti Baena (2016), Marialva Barbosa (2016), Thomaz Souto Corrêa (2013), Newton Dângelo (2013), Doris Fagundes Haussen (2001), Tania Regina de Luca (2008), Ana Paula Goulart Ribeiro (2006), among others. In racial issues and the way Revista do Rádio spoke about the color of Angela’s skin, we approached the discussions with Renato Ortiz (1985), Adilson Moreira (2019), Silvio Almeida (2018) and Sueli Carneiro (2011).